Comparative assessment of efficacy and toxicity of R-DA-EPOCH and R-mNHL-BFM-90 induction courses in the treatment of patients with diffuse large B-cell lymphoma with poor prognostic factors in a randomized multicenter clinical trial “DLBCL-2015” - M. O. Bagova; A. U. Magomedova; S. K. Kravchenko; Ya. K. Mangasarova; O. V. Margolin; E. S. Nesterova; L. G. Gorenkova; A. E. Misyurina; E. A. Fastova; F. E. Babaeva; K. A. Sychevskaya; S. M. Kulikov; et al. (Онкогематология)
Background. Diffuse large B-cell lymphoma (DLBCL) is one of the most common and aggressive tumors of the lymphatic system. Despite the frequency of occurrence, there is no single algorithm for treating DLBCL patients with poor prognostic factors. R-CHOP therapy does not allow achieving long-term complete remissions. Therefore, there is a need for second and subsequent lines of therapy. At the same time, the effectiveness of each subsequent therapy is low, while the toxicity increases. There are many randomized trials of the DLBCL treatment; however, there are only a few studies on the comparative efficacy of high-dose chemotherapy at the induction stage.The objective of the study: the evaluation of the effectiveness and toxicity of R-DA-EPOCH and R-mNHL-BFM-90 induction courses in DLBCL patients with poor prognostic factors in a randomized multicenter clinical trial “DLBCL-2015”.Materials and methods. As of April 2021, 140 patients from 13 medical institutions in Russia were included in the randomized multicenter clinical trial DLBCL-2015. As part of this study, the analysis of pharmacoeconomic factors and effectiveness of combined immunochemotherapy R-DA-EPOCH and R-mNHL-BFM-90 in patients with prognostically unfavorable DLBCL had been performed. From January 2018 to April 2021, this study included 41 patients (21 men, 20 women) with a newly diagnosed DLBCL, with 2 or more factors of an unfavorable prognosis, who were treated at the National Research Center for Hematology of the Ministry of Health of the Russian Federation. Of these, 21 patients received R-DA-EPOCH, and 20, R-mNHL-BFM-90 therapy. Median age for R-DA-EPOCH patients was 52 years (range 30–64); for R-mNHL-BFM-90 patients, 40 years (range 18–60). All patients had high-intermediate and high risk according to the international (IPI) and age-adjusted (aaIPI) prognostic index. The primary protocol endpoints were rates of complete remission, partial remission, disease progression, and hematologic and non-hematologic toxicity. Side effects were assessed in accordance with the Common Terminology Criteria for Adverse Events (CTCAE) criteria.Results. By the end of 6 induction courses, the frequency of achieving complete remission on R-mNHL-BFM-90 therapy was 100 % (20/20) compared to R-DA-EPOCH, where the complete remission rate was 71.4 % (15/21) (p = 0.0097), partial remission and progression were 14.3 % (n = 3) and 14.3 % (n = 3), respectively. Hematological toxicity on therapy according to the R-mNHL-BFM-90 scheme exceeded that on R-DA-EPOCH in terms of myelotoxic agranulocytosis (p = 0.0536), anemia (p = 0.0464) and thrombocytopenia grade III–IV (p = 0.0206). When assessing non-hematological toxicity at the compared courses, no statistically significant differences were noted, all complications occurred with the same frequency.Conclusion. Treatment according to the R-mNHL-BFM-90 protocol is highly effective as first line therapy in high-intermediate and high-risk DLBCL patients. The hematologic toxicity is higher on the R-mNHL-BFM-90 than on the R-DA-EPOCH therapy, but it is acceptable. Non-hematological toxicity in both programs is comparable.